Comparison of acid–base and electrolyte changes following administration of 6% hydroxyethyl starch 130/0.42 in a saline and a polyionic solution in anaesthetized dogs. (May 2018) - Adamik, Katja N.; Obrador, Rafael; Howard, Judith
Abstract: Objective: To evaluate the effects of a 6% hydroxyethyl starch (130/0.42) in either a buffered, electrolyte-balanced (HES-BAL) or saline (HES-SAL) carrier solution on electrolyte concentrations and acid–base parameters in healthy anaesthetized dogs. Study design: Prospective randomised clinical study. Animals: A group of 40 client-owned dogs undergoing general anaesthesia for elective surgical procedures or diagnostic imaging. Methods: During anaesthesia, dogs were intravenously administered 15 mL kg −1 of either HES-SAL ( n = 20) or HES-BAL ( n = 20) over 30–40 minutes. Jugular blood samples were analysed before (T0 ) and 5 minutes (T5 ), 1 hour (T60 ) and 3 hours (T180 ) after fluid administration. Sodium, potassium, chloride, ionised calcium, phosphate, albumin, pH, venous pCO2, base excess (BE), bicarbonate and anion gap were determined and strong ion difference (SID) and total quantity of weak nonvolatile acids were calculated for each time point. Results: Chloride was significantly increased at T5, T60 and T180 compared with T0 after HES-SAL, and was significantly greater after HES-SAL than after HES-BAL at T5 ( p = 0.042). Ionised calcium was significantly decreased at T5 compared with T0 after HES-SAL, and was significantly lower after HES-SAL than after HES-BAL at T5 ( p < 0.001). Bicarbonate was significantly lower after HES-SAL than after HES-BAL at T5 ( p = 0.004) and T60 ( p = 0.032). BE was significantly lower after HES-SAL than after HES-BAL at T5 ( p < 0.001) and T60 ( p = 0.007). SID was significantly decreased after HES-SAL at T5 and T60 compared with T0, and was significantly lower after HES-SAL than after HES-BAL at T5 ( p = 0.027). Mean electrolyte and acid–base parameters remained within or marginally outside of reference intervals. Conclusions and clinical relevance: Changes in both groups were minor and short-lived with either fluid in healthy individuals, but might become clinically relevant with higher fluid doses or in critically ill dogs.